Value, respect, and attachment / Joseph Raz. - Raz, Joseph (John Robert Seeley lectures. ;, 2001)
The book is a contribution to the study of values, as they affect both our personal and our public life. It defends the view that values are necessarily universal, on the ground that that is a condition of their intelligibility. It does, however, reject most common conceptions of universality, like those embodied in the writings on human rights. It aims to reconcile the universality of value with (a) the social dependence of value and (b) the centrality to our life of deep attachments to people and countries alike. Building from there, the book explores personal love, the value of life, and the fundamental duty of respect for people.